The true “punching bag” behind Molière’s The Middle-Class Nobleman - Lekkas, Demetrios E. (Epistēmēs Metron Logos, 2019)
Summary In 1670, the new ballet comedy The middle-class gentleman (Le bourgeois gentilhomme) premiered at the theatre of the French palace before “the Sun King” Louis XIV, on a text by Molière with music by Lully, his permanent collaborator. Both were acting on stage. Since then, no one has raised the question who is the real punching bag of the play’s aggression. The present author decided to research towards understanding it, in order to compose new music responsibly for a performance at the Municipal Regional Theatre of Crete, an island paradoxically connected directly with the initial impetus behind the play’s composition. By studying historical sources, events, linking the circumstances and analyzing in depth the text from a fresh viewpoint with emphasis on certain scenes, he concluded that the target of the playwright’s merciless hard satire was the original composer of the music for the play, because the two of them had entered a period of deep clash for personal, financial and legal differences. The research, with its conclusions regarding the Molièresque attack on Lully, moves on the axes of his humble Italian origins, his greed, the forgery of his family history through the construction of a fake past of nobility, as well as his widely conspicuous effeminacy and open homosexuality, by probing into detailed historical, linguistic, etymological, political and sociological references. The compound historical study of events that took place in the palace and motivated the writing of this play is combined with a social study of the palatine conditions and habits, with juicy references to the customs and etiquette of the wider royal family and the Court, enhanced with anecdotal facts and spicy commentary. The general attempt of this novel multifaceted theatrological viewing is the documentation through a narrative rich in authentic facts about the play, the author, the associate creators and the era, largely unknown to the general public.